Private Financing and the Finnish film industry - Merta, Juuso (My University, 2021)
The Finnish film industry is standing at a delicate cusp. At the time of writing this thesis in 2017, domestic audiences were seeing Finnish films at an all-time high, accounting for 27% of total audience per annum. This number is significant landing Finland in the top five countries for domestic audience attendance in the European market. However, this number has remained started to decline and it would appear that growth in the national market has reached its absolute limit. The only way the Finnish film industry could expand it seems, would be by crossing its national borders through the process of internationalization. The global film industry is fiercely competitive and constantly evolving and relative to countries such as Norway, Sweden and Denmark the budgets of film production are lagging behind. The emergence of private financing in Finnish film production could help in lifting budgets on level with our neighbors, as well as, getting commercially viable domestic films to the international market. The participants for this study were chosen due to their knowledge and expertise regarding film production. Data collection was done through semi-structured interviews. The purpose of this study is to examine private financing in the Finnish film industry. Seen as this is a relatively new phenomenon, it acts both as an interesting subject matter as well as a challenging one, due to there being little to none background data or information regarding it in the national market. This study focused on defining what exactly private financing is, how do the private financiers operate within the Finnish film industry and what do they contribute to the internationalization of Finnish films. The findings aligned to a certain degree with the theory presented by previous research. The findings indicate that there are different forms of private financing; angel investors, crowdfunding, teleoperators, commercial partners, product-placement and private financing funds, such as IPR.VC and Nyland Film Fund. Due to the substantial private investment capabilities of the funds, this thesis focused on them. The key findings indicate that private financing and the internationalization of the Finnish film industry were observed to support one another, and private financing will continue to allow for domestic filmmakers to aspire for bigger and increasingly ambitious productions. This ensures a growing and increasingly international Finnish film industry in the future.

Suomalainen elokuva-ala seisoo herkän käännekohdan edessä. Tutkielman tekemisen ajankohtana, eli vuonna 2017, suomalaiset kävivät katsomassa kotimaisia elokuvia ennätysmäärän. Kaikista elokuvateattereissa katsotuista elokuvista oli peräti 27% oli kotimaisia elokuvia. Luku on merkittävä, suomi sijoittuu viiden parhaan joukkoon kotimaisessa katsojaosuudella Euroopan markkinoilla. Katsojaosuuden kasvu on kuitenkin pysähtynyt ja ja kääntynyt laskuun. Kasvu kotimaisilla markkinoilla näyttää saavuttaneen tietynlaisen ylärajan. Suomalaisen elokuvan kasvun mahdollisuudet näyttäisivät olevan kansainvälisillä markkinoilla. Globaali elokuvateollisuus on äärimmäisen kilpailutettu ja ala kehittyy jatkuvasti. Suhteessa Norjaan, Ruotsiin ja Tanskaan suomalaisten elokuvien budjetit ovat selvästi alhaisemmat. Yksityisen rahoituksen ilmaantuminen suomalaiselle elokuva-alalle voisi mahdollisesti kuroa umpeen tätä eroa meidän naapurimaihimme ja edesauttaa taloudellisesti kannattavien elokuvien päätymistä kansainvälisille markkinoille. Valintaperusteet tutkielman haastateltaviin olivat heidän kokemus ja asiantuntijuus elokuvatuotannossa. Tutkimusaineisto kerättiin tässä tutkimuksessa teemahaastatteluista. Tutkielmantarkoitus oli tarkastella yksityistä rahoitusta suomalaisella elokuva-alalla. Yksityinen rahoitus on suhteellisen uusi ilmiö ja osoittautui sekä mielenkiintoiseksi ja haastavaksi aiheeksi, sillä kotimaista aineistoa siitä ei ollut saatavilla kovinkaan paljon. Tutkielma keskittyi määrittelemään mitä tarkalleen yksityinen rahoitus on, miten yksityiset rahoittajat toimivat alalla ja miten yksityinen rahoitus auttaa suomalaisen elokuva kansainvälistymistä. Tutkimuksen tulokset olivat jokseenkin yhdenmukaisia teorian kanssa. Tulokset osoittivat, että yksityisellä rahoituksella on eri muotoja; enkelisijoittajia, joukkorahoitusta, teleoperaattoreita, taloudellisia kumppaneita, tuotesijoittelua ja yksityisiä sijoitusrahastoja kuten IPR.VC ja Nyland Film Fund. Tämä tutkimus keskittyi etenkin yksityisiin sijoitusrahastoihin heidän merkittävien sijoittamismahdollisuuksien perusteella. Avain tulokset osoittivat, että yksityinen rahoitus ja kansainvälistyminen tukivat toisiaan. Yksityinen rahoitus edesauttaa kotimaisia elokuvantekijöitä tavoitella suurempia ja kunnianhimoisempia tuotantoja, varmistaen elinvoimaisen ja kansainvälisemmän elokuva-alan tulevaisuudessa.
Keywords: Private financing, film industry, internationalization